2020
DOI: 10.15562/bmj.v9i3.1969
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome of COVID-19 infection in Type 2 Diabetes Mellitus: a preliminary data from a tertiary hospital in Jakarta during the early days of the pandemic

Abstract: Introduction:This study aimed to review the clinical characteristics and outcomes of COVID-19 patients presented with in-hospital hyperglycemia or pre-existing type 2 diabetes (T2DM). Methods: This is a retrospective study conducted in Fatmawati General Hospital, Indonesia, from March 18th-Apr 30th, 2020. We reviewed medical records of 27 COVID-19 patients presented with either in-hospital hyperglycemia (11, 12.2%) or pre-existing T2DM (16, 17.8%) from a total of 90 confirmed COVID-19 cases admitted in our hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to the preliminary data obtained from Fatmawati Central General Hospital, Jakarta, Indonesia, it was found that 16 patients who were diagnosed with COVID-19 also had T2DM. Furthermore, the data reported that 68.8% of these patients were deceased (Kshanti et al 2020, Harbuwono et al 2022. COVID-19 patients with T2DM reportedly accounted for 36.4% of the positive cases in Jakarta, according to the data on 738 cases.…”
Section: Introductionmentioning
confidence: 97%
“…According to the preliminary data obtained from Fatmawati Central General Hospital, Jakarta, Indonesia, it was found that 16 patients who were diagnosed with COVID-19 also had T2DM. Furthermore, the data reported that 68.8% of these patients were deceased (Kshanti et al 2020, Harbuwono et al 2022. COVID-19 patients with T2DM reportedly accounted for 36.4% of the positive cases in Jakarta, according to the data on 738 cases.…”
Section: Introductionmentioning
confidence: 97%
“… 3 , 4 Our preliminary data in early pandemic documented half of individuals with diabetes admitted to our hospital due to COVID‐19 were in critical diseases with a mortality rate of over 60% in this group. 5 Identifying individuals with diabetes who are at higher risk of having clinical deterioration is of clinical importance.…”
Section: Introductionmentioning
confidence: 99%